Susceptibility to methicillin and vancomycin in Staphylococcus aureus isolated from blood cultures - Maribel Josefina Castellano-González; Romer Moisés Franquis-Rodríguez; Armindo José Perozo-Mena; Isabelle Virginia Sandoval-Castellano (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
To determine susceptibility to methicillin and vancomycin in blood-isolated strains of Staphylococcus aureus isolated from blood cultures, patient records entered in the Intensive Care Units of the Autonomous Hospital University Service of Maracaibo were analyzed during the period January 2011-December 2015. 35,341 blood cultures were processed; 5.072 (14,35%) were positive; in 455 (8.97%)96 strains of Staphylococcus aureus (21.09%) were isolated, of which 78 (81.25%) were resistant and 18 (18.75%), sensitive to methicillin. All isolates were sensitive to vancomycin. 61.45% of the strains expressed multi-resistance. No statistically significant difference in the frequency of isolation of Staphylococcus aureus per year, age and sex of the patient (p > 0.05) was found; but if according to the type of unit and the presence of antimicrobial co-resistance (p ˂ 0.05). The high levels of methicillin resistance and the evidence of vancomycin-sensitive phenotypes with high minimum inhibitory concentration values (>1 µg/ml), require systematic monitoring of the antimicrobial susceptibility pattern in order to guide clinicians to choose appropriate empirical therapy, contributing to the continuous strengthening of standard precautions and the establishment of local policies for the administration and regulation of the use of antimicrobials.